Low-temperature sintered barium titanate-based multilayer dielectric energy storage ceramic and preparation method thereof
By doping BiDyO3 and Bi(Li1/2Nb1/2)O3 composite perovskite system in BaTiO3-based dielectric ceramics, the sintering temperature is reduced and energy storage performance is improved, and the existing barium titanate-based ceramics has been solved, and a high-efficiency and low-cost high-power pulse power supply material is achieved.
Patent Information
- Application Number
- CN202510126543.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-27
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-27
AI Technical Summary
The high sintering temperature of existing barium titanate-based ceramics leads to high production costs and insufficient energy storage density, limiting their application in high-power pulse power supplies.
By doping BiDyO3 and Bi(Li1/2Nb1/2)O3 composite perovskite system in BaTiO3-based dielectric ceramic components, the sintering temperature is reduced, and the breakdown field strength and energy storage density are improved.
Low-temperature sintering (960~1060oC), improved energy storage density (6.5~12.2 J/cm3) and energy storage efficiency (90.0~96.5%), and was suitable for high-power pulse power supply field.
Smart Images

Figure CN119822815A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of functional ceramics, and in particular to a low-temperature sintered barium titanate-based multilayer dielectric energy storage ceramic and a preparation method thereof. Background Art
[0002] As the core energy storage device of high-power pulse power supply, dielectric capacitor has the advantages of high power density, ultra-fast charge and discharge capability, excellent thermal stability, and strong anti-aging. It plays a vital role in the development of military equipment and the realization of scientific research technology, such as pacemakers, camera flash, nuclear effect simulation, metal forming and hybrid electric vehicles.
[0003] As pulse power devices develop towards miniaturization, lightness and low cost, it is increasingly urgent to develop economical high-energy-density dielectric materials. In the field of dielectric energy storage materials, there are four major types of dielectric materials that can be used for energy storage: linear dielectrics (LD), ferroelectrics (FE), relaxor ferroelectrics (RFE) and antiferroelectrics (AFE). Barium titanate (BaTiO3)-based ceramics are one of the high-quality candidate materials for the preparation of ceramic capacitors due to their excellent electrical properties, including high dielectric constant and excellent ferroelectricity. Traditional barium titanate-based ceramics are ferroelectrics with high sintering temperatures, which are higher than 1150°C. o C; low energy storage density, about 0.3J / cm 3 , it is difficult to meet the needs of modern industry, and it is necessary to improve its performance.
[0004] Doping modification is the most effective means to reduce the sintering temperature of BaTiO3-based dielectric ceramics and improve their energy storage performance. 0.5 Nb 0.5 )O3 composite perovskite system, BaTiO3-xBi(Li 0.5 Nb 0.5 ) The sintering temperature of O3-based dielectric ceramics was reduced to 1150 ° C, and the energy storage density was increased to 4.5 J / cm 3 (ACS Appl. Energy Mater. 2019, 2, 8, 5499–5506); In addition, some researchers also used low-melting-point B2O3-Na2B4O7-Na2SiO3 glass powder doping, which not only effectively reduced the 0.85BaTiO3-0.15Bi(Mg 2 / 3 Nb 1 / 3 )O3 ceramic sintering temperature (750-1350 o C), and also improves its breakdown field strength, which can reach 220 kV / cm and energy storage density of about 1.26 J / cm 3(J. Adv. Dielect. 2018, 8, 1850041). These works all show that BaTiO3-based ceramics have great application potential in the field of dielectric energy storage, but their high sintering temperature leads to high production costs and energy storage density that does not meet application requirements, which seriously limits their application in high-power pulse power supplies. Summary of the invention
[0005] In view of the above problems, the present invention provides a low-temperature sintered barium titanate-based multilayer dielectric energy storage ceramic and a preparation method thereof. By doping BiDyO3 and Bi(Li 1 / 2 Nb 1 / 2 )O3 composite perovskite system, which reduces the sintering temperature of BaTiO3-based dielectric energy storage materials and improves their breakdown field strength and energy storage performance; it provides a high-performance material to meet the development of high-power dielectric energy storage components such as pulse power supplies.
[0006] In a first aspect, the present invention provides a low temperature sintered barium titanate-based multilayer dielectric energy storage ceramic, wherein the chemical formula of the barium titanate-based dielectric ceramic is (1-xy)BaTiO3-yBiDyO3-xBi(Li 1 / 2 Nb 1 / 2 )O3, where 0 < x< 0.1, 0< y< 0.1.
[0007] Preferably, x is 0.04-0.07 and y is 0.03.
[0008] In the present invention, by doping BiDyO3 and Bi(Li 1 / 2 Nb 1 / 2 )O3 composite perovskite system, reducing its sintering temperature, and at the same time greatly improving the breakdown field strength and energy storage density of BaTiO3-based dielectric ceramics.
[0009] Preferably, the densification sintering temperature of the low-temperature sintered barium titanate-based multilayer dielectric energy storage ceramic is 960 to 1060 o C.
[0010] Preferably, the energy storage density of the low-temperature sintered barium titanate-based multilayer dielectric energy storage ceramic is 6.5-12.2 J / cm 3 , the energy storage efficiency is 90.0~96.5%.
[0011] In a second aspect, the present invention provides a method for preparing the low-temperature sintered barium titanate-based multilayer dielectric energy storage ceramic, comprising the following steps:
[0012] (1) Barium titanate (BaTiO3), niobium pentoxide (Nb2O5), lithium oxide (Li2O), bismuth oxide (Bi2O3), and dysprosium oxide (Dy2O3) were selected as raw materials and the reaction mixture was prepared according to the chemical formula (1-xy)BaTiO3-yBiDyO3-xBi(Li 1 / 2 Nb 1 / 2 )O3, wherein y=0~0.1, x=0~0.1, is weighed, mixed evenly with a solvent, a dispersant, a binder and a plasticizer, and then cast to obtain a cast green film A.
[0013] (2) Slicing the obtained cast green film A to obtain a cast green film B, printing electrodes on the surface of the cast green film B by screen printing to obtain a green film printed with electrodes, and hot pressing and laminating the green film printed with electrodes by hot pressing and laminating technology to obtain a ceramic green film C.
[0014] (3) The multilayer ceramic green body C is subjected to plastic disassembly and sintering to obtain the barium titanate-based multilayer dielectric ceramic D.
[0015] (4) The barium titanate-based multilayer ceramic D is polished and coated with terminal electrodes to obtain the barium titanate-based multilayer dielectric energy storage ceramic.
[0016] Preferably, in step (1), the raw materials are in accordance with the chemical formula (1-xy)BaTiO3-yBiDyO3-xBi(Li 1 / 2Nb 1 / 2 )O3 is weighed, and the ratio of the casting slurry is: powder is 100 wt%, the added amount of binder is 4~10 wt%, the solvent is 30~50 wt%, the dispersant is 0.6~1.1 wt%, and the plasticizer is 2~5 wt%.
[0017] The binder is polyvinyl butyral (PVB) with a molecular weight of 70,000-270,000; the solvent is a mixed solvent of p-xylene (30%) and anhydrous ethanol (70%), or a mixed solvent of butanone (40%) and anhydrous ethanol (60%), or a mixed solvent of butanone (88.6%) and water (11.4%), or a mixed solvent of anhydrous ethanol (68%) and toluene (32%), or a mixed solvent of anhydrous ethanol (27%) and trichloroethylene (63%), or a mixed solvent of n-acetone (88%) and butanone (12%), or a mixed solvent of acetone (88%) and toluene (12%), or p-xylene (17 %) and n-acetone (83%), the above percentages are all volume fractions; the dispersant is soybean food oil, peanut oil or fish oil; the plasticizer is a mixture of dibutyl phthalate (DBP) and polyethylene glycol (PEG-400), or a mixture of butyl benzyl phthalate (BBP) and polyethylene glycol (PEG-400), the mass ratio of DBP to PEG-400, and the mass ratio of BBP to PEG-400 are both 1:1.
[0018] The above raw materials are placed in a ball mill for mixing at a rotation speed of 220 to 300 rpm for 6 to 12 hours, and the grinding balls used are zirconia balls.
[0019] Preferably, in step (2), the thickness of the cast green film A is 10 to 50 microns; the electrode in the screen printing is an Ag-Pd electrode or a Cu electrode; the hot pressing temperature in the lamination is 60 ~80 o C, insulation time 1~5min.
[0020] Preferably, in step (3), the temperature of the plastic discharge is 400-600°C and the time is 1-2 hours;
[0021] Preferably, in step (3), the sintering process is to increase the temperature to 960-1060° C. at a heating rate of 3-4° C. / min at room temperature and keep the temperature for 1-3 hours.
[0022] Preferably, in step (4), the terminal electrode is a nickel electrode, a copper electrode or a silver electrode.
[0023] In a third aspect, the present invention provides a low-temperature sintered barium titanate-based multilayer dielectric component, comprising the above-mentioned low-temperature sintered barium titanate-based multilayer dielectric energy storage ceramic, and electrodes distributed on the surface of the barium titanate-based multilayer dielectric energy storage ceramic.
[0024] The present invention has the following beneficial effects:
[0025] Compared with the prior art, the present invention is to dope BiDyO3 and Bi(Li 1 / 2 Nb 1 / 2)O3 composite perovskite system, effectively reducing the sintering temperature of BaTiO3 ceramics and obtaining excellent energy storage density (up to 10.1 J / cm 3 ) and energy storage efficiency (energy storage efficiency can reach 96.5%) (1-xy)BaTiO3-yBiDyO3-xBi(Li 1 / 2 Nb 1 / 2 )O3-based multilayer dielectric energy storage materials, in which Bi(Li 1 / 2 Nb 1 / 2 )O3 can effectively reduce the sintering temperature of ceramics; while the introduction of BiDyO3 can not only reduce the sintering temperature, but also effectively improve the breakdown field strength of ceramics. The obtained material has the advantages of low cost, high voltage resistance, lead-free and environmental protection, high energy storage density and energy storage efficiency, and is suitable for the field of high-power pulse power supply, with very important application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0027] Figure 1 For Example 1, (1-xy)BaTiO3-yBiDyO3-xBi(Li 1 / 2 Nb 1 / 2 )XRD pattern of O3-based dielectric energy storage materials, where x=0.04, y=0.03.
[0028] Figure 2 For Example 1, (1-xy)BaTiO3-yBiDyO3-xBi(Li 1 / 2 Nb 1 / 2 )SEM image of O3-based dielectric energy storage material, where x=0.04, y=0.03.
[0029] Figure 3 For Example 1, (1-xy)BaTiO3-yBiDyO3-xBi(Li 1 / 2 Nb 1 / 2 )Dielectric-temperature spectrum of O3-based dielectric energy storage materials, where x=0.04 and y=0.03.
[0030] Figure 4 For Example 1, (1-xy)BaTiO3-yBiDyO3-xBi(Li 1 / 2 Nb 1 / 2 )Unipolar hysteresis loop of O3-based dielectric energy storage material, where x=0.04 and y=0.03.
[0031] Figure 5 For Example 2, (1-xy)BaTiO3-yBiDyO3-xBi(Li 1 / 2 Nb 1 / 2 )XRD pattern of O3-based dielectric energy storage materials, where x=0.06, y=0.03.
[0032] Figure 6 For Example 2, (1-xy)BaTiO3-yBiDyO3-xBi(Li 1 / 2 Nb 1 / 2 )SEM image of O3-based dielectric energy storage material, where x=0.06, y=0.03.
[0033] Figure 7 For Example 2, (1-xy)BaTiO3-yBiDyO3-xBi(Li 1 / 2 Nb 1 / 2 )Dielectric-temperature spectrum of O3-based dielectric energy storage materials, where x=0.06 and y=0.03.
[0034] Figure 8 For Example 2, (1-xy)BaTiO3-yBiDyO3-xBi(Li 1 / 2 Nb 1 / 2 )Unipolar hysteresis loop of O3-based dielectric energy storage material, where x=0.06 and y=0.03.
[0035] Fig. 9 For Example 3, (1-xy)BaTiO3-yBiDyO3-xBi(Li 1 / 2 Nb 1 / 2 )XRD pattern of O3-based dielectric energy storage materials, where x=0.07, y=0.03.
[0036] Fig.10 For Example 3, (1-xy)BaTiO3-yBiDyO3-xBi(Li 1 / 2 Nb 1 / 2 )SEM image of O3-based dielectric energy storage material, where x=0.07, y=0.03.
[0037] Fig.11 For Example 3, (1-xy)BaTiO3-yBiDyO3-xBi(Li 1 / 2 Nb 1 / 2 )Dielectric-temperature spectrum of O3-based dielectric energy storage materials, where x=0.07 and y=0.03.
[0038] Fig.12For Example 3, (1-xy)BaTiO3-yBiDyO3-xBi(Li 1 / 2 Nb 1 / 2 )Unipolar hysteresis loop of O3-based dielectric energy storage material, where x=0.07 and y=0.03.
[0039] Fig.13 For comparison with Example 1, the dielectric temperature spectrum of pure BaTiO3-based dielectric energy storage material.
[0040] Fig.14 For comparison with Example 1, the unipolar hysteresis loop of pure BaTiO3-based dielectric energy storage material.
[0041] Fig.15 For Comparative Example 2, (1-xy)BaTiO3-yBiDyO3-xBi(Li 1 / 2 Nb 1 / 2 )Dielectric-temperature spectrum of O3-based dielectric energy storage materials, where x=0.00, y=0.03.
[0042] Fig.16 For Comparative Example 2, (1-xy)BaTiO3-yBiDyO3-xBi(Li 1 / 2 Nb 1 / 2 )Unipolar hysteresis loop of O3-based dielectric energy storage material, where x=0.00, y=0.03. DETAILED DESCRIPTION
[0043] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.
[0044] The present invention provides a low temperature sintered barium titanate-based multilayer dielectric energy storage ceramic, the molecular formula of which is (1-xy)BaTiO3-yBiDyO3-xBi(Li 1 / 2 Nb 1 / 2 )O3, wherein 0 < x < 0.1, 0 < y < 0.1. The sintering temperature of the multilayer dielectric energy storage ceramic is low, about 960~1060 o C, excellent energy storage characteristics, energy storage density is 6.5~12.2 J / cm 3 , the energy storage efficiency is 96.5%. In particular, the (1-xy)BaTiO3-yBiDyO3-xBi(Li 1 / 2 Nb 1 / 2 )O3-based ceramics have a strong breakdown field, high energy storage density and efficiency, and are low in price. They are a low-cost, high-performance pulse high-power power supply component material.
[0045] Example 1
[0046] Preparation of (1-xy)BaTiO3-yBiDyO3-xBi(Li 1 / 2 Nb 1 / 2 )O3, where x=0.04, y=0.03.
[0047] The ceramic material of this embodiment is prepared by a solid phase sintering method, specifically according to the following steps:
[0048] (1) According to the molecular formula: (1-xy)BaTiO3-yBiDyO3-xBi(Li 1 / 2 Nb 1 / 2 )O3 where x=0.04, y=0.03 is used for batching calculation. The required raw materials are: barium titanate (BaTiO3), niobium pentoxide (Nb2O5), lithium oxide (Li2O), bismuth oxide (Bi2O3), and dysprosium oxide (Dy2O3). An electronic balance is used for weighing with an accuracy of 0.001g.
[0049] (2) Mix the weighed raw materials and put them into a nylon tank, add anhydrous ethanol not higher than 1 / 3 of the tank height to mix the materials, use zirconium oxide balls as the medium, put the nylon tank on a horizontal ball mill and mix for 8 hours, the zirconium oxide balls have three sizes of 3mm, 5mm and 8mm, and the mass ratio is 3:4:3. Pour the ball-milled slurry into a tray and put it into an oven for drying; grind the dried powder to obtain fine ceramic powder.
[0050] (3) A casting slurry was prepared according to the mass ratio of ceramic powder: PVB: solvent: dispersant: plasticizer of 100:4.2:35:0.61:2.4, wherein the solvent was a mixed solvent of butanone (40%) and anhydrous ethanol (60%), the dispersant was fish oil, and the plasticizers were dibutyl phthalate (DBP) and polyethylene glycol (PEG-400).
[0051] (4) The casting slurry was poured into a casting machine with a blade height of 135 μm and a speed of 0.7 cm / s to obtain a casting film.
[0052] (5) Cut the film strip and screen-print platinum electrodes; stack the film strips with printed electrodes.
[0053] (6) Slice the stacked sheets and perform plastic removal, where the plastic removal temperature is 600 o C, the holding time is 1 hour.
[0054] (7) The molded green body was sintered in an atmospheric atmosphere at a sintering temperature of 1060°C for 3 hours. The sample was taken out after naturally cooling to room temperature.
[0055] The prepared barium titanate-based ceramic material was polished to expose the inner electrode; then a silver-terminal electrode was coated on the exposed inner electrode to obtain a barium titanate-based multilayer dielectric energy storage material, and the structure and performance tests were carried out.
[0056] Example 2
[0057] Preparation of (1-xy)BaTiO3-yBiDyO3-xBi(Li 1 / 2 Nb 1 / 2 )O3, wherein x=0.06, y=0.03. Except for the different values of x in step (1) and the sintering temperature in step (7), the other steps are the same as those in Example 1. The sintering temperature of this sample is 1030°C and the sintering time is 3 hours.
[0058] Example 3
[0059] Preparation of (1-xy)BaTiO3-yBiDyO3-xBi(Li 1 / 2 Nb 1 / 2 )O3, wherein x=0.07, y=0.03. Except for the different values of x in step (1) and the sintering temperature in step (7), the other steps are the same as those in Example 1. The sintering temperature of this sample is 980°C and the sintering time is 3 hours.
[0060] Comparative Example 1
[0061] (1) According to the molecular formula: (1-xy)BaTiO3-yBiDyO3-xBi(Li 1 / 2 Nb 1 / 2 )O3, where x=0.00, y=0.00 for ingredient calculation, the only raw material required is barium titanate (BaTiO3).
[0062] The sintering temperature of step (7) is 1360 o C, keep warm for 2 hours, and the other preparation processes are the same as in Example 1.
[0063] The prepared BaTiO3 ceramics were subjected to performance tests.
[0064] Comparative Example 2
[0065] (1) According to the molecular formula: (1-xy)BaTiO3-yBiDyO3-xBi(Li 1 / 2 Nb 1 / 2 )O3, where x=0.00, y=0.03 is used for ingredient calculation. The required raw materials are: barium titanate (BaTiO3), bismuth oxide (Bi2O3), and dysprosium oxide (Dy2O3). An electronic balance is used for weighing with an accuracy of 0.001g.
[0066] The sintering temperature of step (7) is 1200o C, keep warm for 2 hours, and the other preparation processes are the same as in Example 1.
[0067] The prepared (1-xy)BaTiO3-yBiDyO3-xBi(Li 1 / 2 Nb 1 / 2 )O3 ceramics, where x=0.00, y=0.03 ceramics were tested for performance.
[0068] The (1-xy)BaTiO3-yBiDyO3-xBi(Li 1 / 2 Nb 1 / 2 )O3-based dielectric energy storage materials and the sintering temperatures and properties of the ceramics of Comparative Examples 1-2 are compared, and the results are shown in Table 1. From Examples 1 to 3, it can be seen that (1-xy)BaTiO3-yBiDyO3-xBi(Li 1 / 2 Nb 1 / 2 ) The sintering temperature of O3 ceramics is 960~1060 o C, where 0<x<0.1 mol, 0<y<0.1 mol; much lower than the sintering temperature of BaTiO3 provided in Comparative Example 1 and the (1-y)BaTiO3-yBiDyO3 ceramic provided in Comparative Example 2, which are 1360 o C and 1200 o C. In addition, the breakdown field strength, energy storage density and energy storage efficiency of the embodiment ceramics are much greater than those of BaTiO3 and (1-y)BaTiO3-yBiDyO3 ceramics.
[0069] Table 1 (0.97-x)BaTiO3-0.03BiDyO3-xBi(LiNb) 1 / 2 Comparison of performance of O3-based dielectric energy storage materials
[0070]
[0071] Figure 1-12 The phase structure and properties of the ceramics of Examples 1-3, wherein the components of Examples 1, 2 and 3 are (1-xy)BaTiO3-yBiDyO3-xBi(Li 1 / 2 Nb 1 / 2 )O3where x=0.04, y=0.03, x=0.06, y=0.03 and x=0.07, y=0.03. Figure 1 , 5 9 and 10 are XRD diagrams of the ceramics of Examples 1-3, respectively, indicating that they are pure perovskite structures. Figure 2 , 6 10 and 11 are SEM images of the ceramics of Examples 1-3, respectively, which illustrate that the ceramic samples are dense and the grain size is about 2 μm. Figure 3 ,7 1 and 11 are the dielectric temperature spectra of the ceramics of Examples 1-3, indicating that their sintering temperatures are between 960 and 1060 o C. Figure 4 , 8 1 and 12 are the unipolar hysteresis loops of the ceramics of Examples 1-3, indicating that the hysteresis is very small. Therefore, Examples 1-3 are sintered at temperatures of 960°C to 1060°C. o The ceramics of C have high density and uniform grain size distribution. In addition, the hysteresis of their hysteresis loops is very small. By comparing Examples 1-3, it can be seen that with the increase of x content, the sintering temperature of the ceramic samples is significantly reduced. In addition, with the increase of x content, the energy storage efficiency of the ceramic samples is also increased accordingly.
[0072] Figure 13-16 The phase structure and performance of the comparative ceramics are shown in Figure 1. Comparative Example 1 is pure BaTiO3, where x and y are 0.00 respectively. Fig.13 The dielectric temperature spectrum of pure BaTiO3-based dielectric energy storage materials shows that the sintering temperature of pure BaTiO3 ceramics is relatively high, about 1360 o C. And the hysteresis of the hysteresis loop is large, such as Fig.14 As shown. Similar to Comparative Example 1, Fig.15 Comparative Example 2 (1-xy)BaTiO3-yBiDyO3-xBi(Li 1 / 2 Nb 1 / 2 ) Dielectric-temperature spectrum of O3-based dielectric energy storage materials, where x=0.00, y=0.03, and its sintering temperature is 1200 o C. And the hysteresis of its hysteresis loop is also large, such as Fig.16 shown.
[0073] In addition to the above embodiments and comparative examples, the applicant also conducted the following comparative tests:
[0074] 1) Prepared (1-xy)BaTiO3-yBiDyO3-xBi(Li 1 / 2 Nb 1 / 2 )O3-based ceramics. 1 / 2 Nb 1 / 2 ) The high O3 content causes a large amount of liquid phase to appear in the ceramic during the sintering process, and the sintered ceramics will warp, making it impossible to perform performance tests.
[0075] 2) Prepared (1-xy)BaTiO3-yBiDyO3-xBi(Li 1 / 2 Nb 1 / 2 )O3-based ceramics. With x=0.2, y=0.03 (1-xy)BaTiO3- yBiDyO3-xBi(Li1 / 2 Nb 1 / 2 )O3-based ceramics, x = 0.1, y = 0.15 (1-xy)BaTiO3-yBiDyO3-xBi(Li 1 / 2 Nb 1 / 2 )O3-based ceramics are also prone to warping due to the high liquid content, and performance testing is not possible. 1 / 2 Nb 1 / 2 )The suitable composition of O3-based ceramics is 0<x<0.1 mol, 0 <y<0.1 mol.
[0076] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A low-temperature sintered barium titanate-based multilayer dielectric energy storage ceramic, characterized in that: The chemical formula of the ceramic is (1-xy)BaTiO3-yBiDyO3-xBi(Li 1 / 2 Nb 1 / 2 )O3, where 0 < x< 0.1, 0 < y< 0.
1.
2. The low temperature sintered barium titanate-based multilayer dielectric energy storage ceramic according to claim 1, characterized in that: Among them, x is 0.04~0.07, and y is 0.
03.
3. The low temperature sintered barium titanate-based multilayer dielectric energy storage ceramic according to claim 1 or 2, characterized in that: The densification sintering temperature of the low-temperature sintered barium titanate-based multilayer dielectric energy storage ceramic is 960 to 1060 o C, energy storage density is 6.5~12.2 J / cm 3 , the energy storage efficiency is 90.0~96.5%.
4. The method for preparing low temperature sintered barium titanate-based multilayer dielectric energy storage ceramics according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) Barium titanate, niobium pentoxide, lithium oxide, bismuth oxide, and dysprosium oxide are selected as raw materials and prepared according to the chemical formula (1-xy)BaTiO3-yBiDyO3-xBi(Li 1 / 2 Nb 1 / 2 )O3, wherein y=0~0.1, x=0~0.1, after weighing, mixing evenly with solvent, dispersant, binder and plasticizer, and then casting to obtain cast green film A; (2) Slicing the obtained cast green film A to obtain a cast green film B, printing electrodes on the surface of the cast green film B by screen printing to obtain a green film printed with electrodes, and hot pressing and laminating the green film printed with electrodes by hot pressing and laminating technology to obtain a ceramic green film C; (3) Extruding and sintering the multilayer ceramic green body C to obtain a barium titanate-based multilayer dielectric ceramic D; (4) The barium titanate-based multilayer ceramic D is polished and coated with terminal electrodes to obtain the barium titanate-based multilayer dielectric energy storage ceramic.
5. The method for preparing low temperature sintered barium titanate-based multilayer dielectric energy storage ceramics according to claim 4, characterized in that: In step (1), the raw materials are prepared according to the chemical formula (1-xy)BaTiO3-yBiDyO3-xBi(Li 1 / 2 Nb 1 / 2 )O3 is weighed, and the ratio of the casting slurry is: powder is 100 wt%, the added amount of binder is 4~10 wt%, the solvent is 30~50 wt%, the dispersant is 0.6~1.1 wt%, and the plasticizer is 2~5 wt%.
6. The method for preparing low temperature sintered barium titanate-based multilayer dielectric energy storage ceramics according to claim 5, characterized in that: The binder is polyvinyl butyral; the dispersant is soybean food oil, peanut oil or fish oil; and the plasticizer is a mixture of dibutyl phthalate and polyethylene glycol, or a mixture of butyl benzyl phthalate and polyethylene glycol.
7. The method for preparing low temperature sintered barium titanate-based multilayer dielectric energy storage ceramics according to claim 4, characterized in that: In step (2), the thickness of the cast green film A is 10-50 μm; the electrode in the screen printing is an Ag-Pd electrode or a Cu electrode; the hot pressing temperature in the lamination is 60-80 o C, insulation time 1~5min.
8. The method for preparing low temperature sintered barium titanate-based multilayer dielectric energy storage ceramics according to claim 4, characterized in that: In step (3), the temperature of the plastic discharge is 400-600°C for 1-2 hours; the sintering process is to increase the temperature to 960-1060°C at a heating rate of 3-4°C / min at room temperature and keep the temperature for 1-3 hours.
9. The method for preparing low temperature sintered barium titanate-based multilayer dielectric energy storage ceramics according to claim 4, characterized in that: In step (4), the terminal electrode is a nickel electrode, a copper electrode or a silver electrode.
10. A low temperature sintered barium titanate based multilayer dielectric component, characterized in that: The invention comprises a barium titanate-based multilayer dielectric energy storage ceramic obtained by the preparation method described in any one of claims 1 to 3 or any one of claims 4 to 9, and electrodes distributed on the surface of the barium titanate-based multilayer dielectric energy storage ceramic.
Citation Information
Patent Citations
Composite doped modified Y2Ti2O7 microwave medium ceramic material
CN102153342A
High-temperature X8R type ceramic-capacitor dielectric material and preparation method thereof
CN106348748A
Preparation method of lead-free high-Curie-point BaTiO3-based positive-temperature-coefficient thermal sensitive ceramic
CN106866135A
Method for producing barium titanate powder
KR1020170042477A
Barium titanate and production process thereof
US20030044347A1